2019
DOI: 10.2196/preprints.13853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Attitudes of Therapists and Physicians on the Use of Sex Robots in Sexual Therapy: Online Survey and Interview Study (Preprint)

Abstract: BACKGROUND Various types of robots have already been successfully used in medical care, and the use of new technologies is also playing an increasing role in the area of sexuality. Sex robots are marketed as advanced sex toys and sex dolls with artificial intelligence. Only a few considerations about the therapeutic use of sex robots in sexual therapy are debated in expert discussions. OBJECTIVE … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Recent research has found that the sale of medicines through websites or mobile phone applications increases patients' access to medicines; people buy medicines online because they perceive it to be cheap and convenient compared to buying the same products online, while simultaneously providing greater choice and autonomy (1)(2)(3)(4)(5). Online outlets may also provide an alternative for people who want or need medication, but who have no access to legitimate healthcare channels or prescriptions (5)(6)(7).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Recent research has found that the sale of medicines through websites or mobile phone applications increases patients' access to medicines; people buy medicines online because they perceive it to be cheap and convenient compared to buying the same products online, while simultaneously providing greater choice and autonomy (1)(2)(3)(4)(5). Online outlets may also provide an alternative for people who want or need medication, but who have no access to legitimate healthcare channels or prescriptions (5)(6)(7).…”
Section: Introduction Backgroundmentioning
confidence: 99%